An Analysis of Students’ Language Features Understanding in Narrative Text: A Descriptive Study at SMPN 6 Gunung Talang - Monaliza, Monaliza; Rani, Yati Aisya (Universitas Negeri Padang, 2024)
This study aimed to analyze students' understanding of language features and the most difficult part of language features in narrative texts at SMPN 6 Gunung Talang. Descriptive research was the method used in this study with Grade eight students as the population. To determine the sample, the researcher used proportional random sampling where 30 eighth grade students were selected as samples in this study. There were two instruments used in this study which were tests and interviews. The results of the study showed that students' ability to understand language features in narrative texts showed an average score of 35.4. This score indicates that students generally fail to understand language features in narrative texts. Then, the most difficult part of the language features of narrative text for eighth grade students is the simple past tense with a percentage of 77% incorrect answers from 300 question occurrences.